Opportunities and Challenges of AI Adoption in Ugandan Businesses - Yassin, Abdulnassir (The Indonesian Institute of Science and Technology Research, 2025)
The integration of Artificial Intelligence (AI) in business sectors has brought transformative changes across the globe. Uganda, as a developing country with a predominantly young population, presents both unique opportunities and challenges for AI implementation. This study explores the demographic, infrastructural, and policy-related factors influencing AI adoption in Ugandan businesses. Using a mixed-methods approach, including literature reviews, demographic analysis, case studies, and policy evaluation, the study reveals that while AI has the potential to revolutionize sectors like agriculture, retail, and services, its success depends heavily on inclusive policy, digital literacy, infrastructure development, and localized innovation. The paper concludes by recommending targeted policy reforms, capacity building, and private-sector partnerships to ensure equitable and efficient AI deployment.